A simple aptamer-based fluorescent assay for the detection of Aflatoxin B1 in infant rice cereal. (15th January 2017) - Chen, Lu; Wen, Fang; Li, Ming; Guo, Xiaodong; Li, Songli; Zheng, Nan; Wang, Jiaqi
Highlights: A fluorescent aptasensor has been developed for detection of AFB1 in infant food. TAMRA at the end of probe plays as a quencher in fluorescent aptasensor. The signal increases with increasing the concentration of the AFB1. The sensor provides rapid, sensitive, and detection of AFB1 . This method has the potential for AFB1 analysis in diverse foods. Abstract: A fluorescent assay for the rapid, sensitive and specific detection of Aflatoxin B1 (AFB1 ) was developed in this study. Initially, a DNA/DNA duplex was formed between a fluorescein-labeled AFB1 aptamer and its partially complementary DNA strand containing a quencher moiety, resulting in fluorescence quenching due to the close proximity of fluorophore and quencher. Upon the addition of AFB1, an aptamer/AFB1 complex was generated to release the quencher-modified DNA strand, thus recovered the fluorescence of fluorescein and enabled quantitative detection for AFB1 by monitoring fluorescence enhancement. Under optimized conditions, this assay exhibited a linear response to AFB1 in the range of 5–100 ng/mL with a detection limit down to 1.6 ng/mL. Trials of this assay in infant rice cereal with satisfactory recovery in the range of 93.0%–106.8%, demonstrate that the new assay could be a potential sensing platform for AFB1 determination in food.